Cravings as a mediator and moderator of drinking outcomes in the COMBINE study. (4th June 2013) - Subbaraman, Meenakshi Sabina; Lendle, Samuel; van der Laan, Mark; Kaskutas, Lee Ann; Ahern, Jennifer
Abstract: Aims: Investigators of the COMBINE (Combining Medications and Behavioral Interventions for Alcoholism) study examined whether combining medications with a behavioral intervention would improve outcomes over monotherapies. Unexpectedly, the combination did not offer any advantage over either treatment alone. This study aimed to explain the lack of incremental benefit offered by the combination over either monotherapy by assessing the role of cravings as a treatment mediator and moderator. Design: Secondary mediation and moderation analyses of COMBINE study data. Setting: Eleven United States academic sites. Participants: A total of 863 patients randomized to one of four treatment groups: naltrexone (100 mg/day; n  = 209), the combined behavioral intervention (CBI, n  = 236), naltrexone and CBI combined ( n  = 213) and placebo naltrexone ( n  = 205). Measurements: Percentage of days abstinent (PDA) measured between 13 and 16 weeks post‐baseline. Cravings, the potential mediator/moderator, were measured at baseline, weeks 4 and 12 using the Obsessive‐Compulsive Drinking Scale. Findings: Compared with placebo, naltrexone, CBI and the combination all increased PDA by an additional 6–10 percentage points for those with high cravings ( P  < 0.05 for all three treatment groups). None had significant effects on PDA for those with low cravings. The effects of all three treatments were mediated at least partially by cravings; craving reduction explained 48–53% of treatment effects ( P  < 0.05 for all three treatment groups). Furthermore, naltrexone appeared to reduce cravings at 4 weeks, while CBI did not reduce cravings until 12 weeks. Conclusions: The Combining Medications and Behavioral Interventions for Alcoholism (COMBINE) naltrexone + CBI combination may not be more beneficial than either monotherapy because craving reduction is a common mechanism of both.